The level of selected motor-cognitive abilities of young female professional dancers in the context of perfectionism - Huzsarska. I.; Blizniak, K.; Przednowek, K. (Journal of Physical Education and Sport, 2023)
Problem Statement Dance is a physical activity that combines multiform movement with synchronization to music. It requires specific cognitive skills and personality traits. The main contribution of this paper was to investigate the relationship between perfectionism and motor-cognitive abilities. Approach: 31 junior female dancers aged 13-16 years participated in the presented study. Dancers are members of two dancing teams, which regularly participate in National Championships, Europe Championships, World Championships and World Cups in Show Dance and Jazz Dance.